Pengaruh Ekstrak Etanol Herba Pecut Kuda Stachytarpheta jamaicensis (l.) Vahl Terhadap Fungsi Hati Dan Kreatinin Urin Mencit Putih Jantan - Elisma Elisma; Deni Kurniati; Helmi Arifin (Jurnal Farmasi Higea, 2010)
Research on the effect of ethanol extract of pecut kuda (Stachytarpheta jamaicensis (L) Vahl) against liver and kidney function in male white mice have been done. Extracts administered orally with various doses of 150, 300 and 600 mg / kg bw once daily for 15, 30 and of 45 days. As a control group used white males mice who were given only 0.5% Na CMC. Activity SGPT and SGOT, creatinine clearance, renal function and the percentage ratio of organ weight were measured. The result showed that the extract at given doses effects liver function (p<0.05) and not effects  the urinary creatinine levels (p> 0.05)